Using oxygen/ozone nanobubbles for in situ oxidation of dissolved hydrogen sulfide at a residential tunnel-construction site. (15th January 2022) - Maie, Nagamitsu; Anzai, Satoshi; Tokai, Kengo; Kakino, Wataru; Taruya, Hiroyuki; Ninomiya, Hideki
Abstract: Hydrogen sulfide (H2 S) is a toxic gas, and considerable research has been conducted for its control and removal from industrial wastewater and sewage water. However, no simple and practical technology is available for degrading H2 S in situ at tunnel constructing sites. On May 11, 2020, an H2 S blowout accident occurred in underground soil at a residential sewer-tunnel construction site in Iwakuni City, Yamaguchi Prefecture, Japan, filling the tunnel with high concentrations of H2 S gas, causing the fatality of one worker owing to emphysema. River water flowing near the site was immediately introduced into the tunnel to trap the H2 S gas, generating 652-m 3 water that contained high concentrations (120 mg/L) of dissolved H2 S in the tunnel. To safely and quickly remove H2 S in situ, the contaminated water was treated with high-density oxygen and ozone nanobubbles (O2 /O3 -HDNBs) generated using the ultrafine pore method. Consequently, H2 S was removed from the contaminated water in 3 days. This is the first successful application of O2 /O3 -HDNB technology for the in situ oxidation of H2 S in environmental water at a construction site. This study reports the practical application of this advanced technology and the system performance. Highlights: An H2 S blowout accident occurred at a residential sewer-tunnel construction site. Nanobubble technology is employed for the first time to oxidize dissolved H2 S in situ. In three days, 31-kg H2 S dissolved in 652-m 3 natural water was oxidized. Minimal post-treatment was required for the treated water.